A Linguagem, o Texto e o Documento no contexto da Ciência da Informação - Cavati Sobrinho, Heliomar; Moraes, João Batista Ernesto de [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2012)
The relation among the concepts text, document and information is discussed, with the aim of clarifying the concept of document, with a focus in the field of economic information organization and management. A document is a medium in which information is recorded and manifested. A document is, thus, material, has a purpose, can be organized and treated for its improved dissemination, and has a specific subject and context.

Se discute la relación entre los conceptos de “texto”,”documento” e “información”, con el objetivo de precisar el concepto de documento, especialmente en el ámbito de la organización y gestión de la información económica. El documento es un soporte en el que está registrada o manifestada una información. El documento, por tanto, es material, posee una intención, puede ser organizado y tratado para su mejor diseminación, presenta una tematicidad y un contexto específicos.
Language, text and document in the context of Information Science
Lenguaje, texto y documento en el contexto de la ciencia de la información
Keywords: Definition; Document; Financial information; Information science; Lenguage; Text